Socio-Demographic Determinants and Hyperglycaemia in Diabetic and Non-Diabetic Patients in Greater Noida, India - Gupta, Shikha; Khan, Azra; Singh, Ranjana (Journal of Neonatal Surgery, 2025)
This study investigated the socio-demographic factors, fasting blood sugar (FBS), hyperglycaemia, and compliance behaviours among diabetic and non-diabetic patients in Greater Noida, Uttar Pradesh, India. Data were collected from 1,073 patients (502 diabetics and 571 non-diabetics) through patient interviews across five hospitals. The study explored various demographic factors such as gender, age, marital status, education, economic status, smoking habits, body mass index (BMI), family type, and physical activity levels. Significant associations were found between these factors and FBS levels, with diabetic patients generally showing higher FBS levels than non-diabetics (P < 0.001). Gender, age group, marital status, and educational status significantly influenced FBS levels (P < 0.05). The study also observed a higher prevalence of hyperglycaemia among diabetic patients, especially in those with high BMI and low physical activity. Smoking was associated with increased hyperglycaemia in diabetic patients (P < 0.001). Further, the study analysed patient compliance to diabetes management regimens (diet, exercise, and medication) based on smoking status and BMI. Diabetic smokers exhibited lower compliance in diet, exercise, and medication compared to non-smokers. Similarly, patients in the overweight and obese categories showed reduced adherence, particularly in exercise and diet. These findings highlight the impact of socio-demographic and lifestyle factors on both the clinical management and self-care behaviours of diabetic patients. In conclusion, this study emphasizes the need for targeted interventions addressing both the socio-demographic determinants and lifestyle behaviours such as smoking and BMI to improve diabetes management. Public health efforts focusing on personalized care plans and promoting adherence to recommended regimens could help mitigate hyperglycaemia and enhance patient outcomes in the region.